Abnormal Lipoproteins Trigger Oxidative Stress-Mediated Apoptosis of Renal Cells in LCAT Deficiency - Monica Gomaraschi; Marta Turri; Arianna Strazzella; Marie Lhomme; Chiara Pavanello; Wilfried Le Goff; Anatol Kontush; Laura Calabresi; Alice Ossoli (MDPI AG, 2023)
Familial lecithin:cholesterol acyltransferase (LCAT) deficiency (FLD) is a rare genetic disease caused by the loss of function mutations in the LCAT gene. LCAT deficiency is characterized by an abnormal lipoprotein profile with severe reduction in plasma levels of high-density lipoprotein (HDL) cholesterol and the accumulation of lipoprotein X (LpX). Renal failure is the major cause of morbidity and mortality in FLD patients; the pathogenesis of renal disease is only partly understood, but abnormalities in the lipoprotein profile could play a role in disease onset and progression. Serum and lipoprotein fractions from LCAT deficient carriers and controls were tested for renal toxicity on podocytes and tubular cells, and the underlying mechanisms were investigated at the cellular level. Both LpX and HDL from LCAT-deficient carriers triggered oxidative stress in renal cells, which culminated in cell apoptosis. These effects are partly explained by lipoprotein enrichment in unesterified cholesterol and ceramides, especially in the HDL fraction. Thus, alterations in lipoprotein composition could explain some of the nephrotoxic effects of LCAT deficient lipoproteins on podocytes and tubular cells.